2019
DOI: 10.1371/journal.pntd.0007115
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards lymphatic filariasis elimination in Ghana from 2000-2016: Analysis of microfilaria prevalence data from 430 communities

Abstract: Background Ghana started its national programme to eliminate lymphatic filariasis (LF) in 2000, with mass drug administration (MDA) with ivermectin and albendazole as main strategy. We review the progress towards elimination that was made by 2016 for all endemic districts of Ghana and analyze microfilaria (mf) prevalence from sentinel and spot-check sites in endemic districts. Methods We reviewed district level data on the history of MDA and outcomes of transmission ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
0
29
0
2
Order By: Relevance
“…In all, 430 communities were surveyed for LF infections as part of a transmission assessment survey in Ghana. Details of this dataset is described by Biritwum et al (2019). Spatial locations of these communities were extracted from multiple sources including Google Earth Pro, Open Street Map, directory of cities and towns (world database) and database of the Ghana National Identi cation Authority card registration projects.…”
Section: Lf Prevalence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 430 communities were surveyed for LF infections as part of a transmission assessment survey in Ghana. Details of this dataset is described by Biritwum et al (2019). Spatial locations of these communities were extracted from multiple sources including Google Earth Pro, Open Street Map, directory of cities and towns (world database) and database of the Ghana National Identi cation Authority card registration projects.…”
Section: Lf Prevalence Datamentioning
confidence: 99%
“…Data on mf cases in Ghana was obtained from published article in peer-reviewed journals (Biritwum et al, 2019: Gyapong et al, 2002. The data spanning 2000 to 2014 contained information on the year samples were collected, number of years of MDA, number of people examined, and number of mf positive recorded for each study community.…”
Section: Lf Prevalence Datamentioning
confidence: 99%
“…Whilst the present study investigated community members with a wide age range (2-86yrs). There are mixed perceptions on whether conducting a school-based or community-based TAS but other authors have drawn attention on possibility of leaving out non-school attendants some of whom might have not received the drugs (Biritwum et al, 2019). For examples in American Samoa, high prevalence of lariasis was observed in community-based assessment (6.2%) than in school-based survey (0.7%) (Sheel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the earlier reports which suggested termination of drug distribution following 5-6 rounds (WHO, 2011), in fact the exact number of treatments to implement such decision was unclear. For example some endemic countries have implemented up to 14 rounds of MDA (Biritwum et al, 2019). The prematurely termination of drug distribution has in part, contributed to rebounce of infection in some endemic countries (Boyd et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…years of annual MDA, such as in Nigeria, Tanzania and Ghana [18][19][20]. In Ghana, after up to 14 rounds of MDA, the transmission of LF still persists in districts with relatively high baseline prevalence [21]. Modelling of LF MDA showed that baseline prevalence is one of the most important factors on impact, along with the number of rounds of MDA [22].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%